PENGARUH DEBT TO EQUITY RATIO, RETURN ON ASSETS DAN CURRENT RATIO TERHADAP DIVIDEND PAYOUT RATIO PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2013-2015 - -, Agung Widjaksono (EKONOMIA, 2018)
The investor invest to a go public company in a form of stocks, by their aim to get profit from the company that they invest in a form of dividend. The investors like companies that are able to distribute dividends well (stable), therefore before investing the investor is have to do an analysis about a ratio to divide the dividend by analyzing the finance ratio such as Debt to Equity Ratio (DER), Return On Assets and Current Ratio toward Dividend Payout Ratio in manufacturing companies listed on BEI period 2013-2015 The purpose of this research is to analyze and to find the influence of Debt to Equity Ratio (DER), Return On Assets (ROA) and Current Ratio (CR) to Dividend Payout Ratio (DPR) either partially or simultaneously at manufacturing companies listed on BEI period 2013-2015.The Population and sample in this research are all manufacturing companies listed on BEI period 2013-2015. The sampling technique used purposive sampling method and obtained a sample of 27 companies. The type of data used is secondary data. Methods of data collection using documentation method. The analysis technique used is multiple linear regression.The results showed that: (1) Debt to Equity Ratio has significant effect to Dividend Payout Ratio. (2) Return On Assets has significant effect to Dividend Payout Ratio. (3) Current Ratio has significant effect to Dividend Payout Ratio. (4) Debt to Equity Ratio, Return On Assets and Current Ratio have significant effect to Dividend Payout Ratio.